PARTNERSHIPS THAT WORK: AN ACADEMIC AND STATE COLLABORATION IN KANSAS. (8th November 2019) - Doll, Gayle; Kaup, Migette; Cornelison, Laci
Abstract: Academic partnership with state government may be a researcher's dream or a tremendous burden. This presentation demonstrates the perspectives of university personnel as well as government leaders when contracts and grants are issued for the provision of research and services. Opportunities and barriers for researchers will be discussed.